2006
DOI: 10.1016/j.euje.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echocardiography: A screening method for pulmonary vein stenosis after catheter ablation of atrial fibrillation

Abstract: TEE identifies significant PV stenosis by assessment of flow characteristics and vessel diameter and can thereby be used as a follow-up tool after catheter ablation of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The prevalence of PV stenosis ranged from 4% to 28% of patients (1–17% of PVs). Whereas most of the studies reported results at the PV level, only two studies also reported results at the patient level 17,24 . The exact prevalence of PV stenosis could not be calculated in two studies 16,23 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of PV stenosis ranged from 4% to 28% of patients (1–17% of PVs). Whereas most of the studies reported results at the PV level, only two studies also reported results at the patient level 17,24 . The exact prevalence of PV stenosis could not be calculated in two studies 16,23 .…”
Section: Resultsmentioning
confidence: 99%
“…Because the PV diameter before and after ablation was not available in most of the studies, we did not evaluate the diagnostic accuracy of TEE using a definition of PV stenosis based on PV ostial size. Furthermore, the lack of clear delineation of the left atrium‐PV junction by TEE may affect the measurements of PV ostial size 17 and make the calculated sensitivity and specificity less reliable. The available studies defined PV stenosis based on percent diameter loss in PV lumen compared to preablation or normal adjacent values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations